Gestion de la biodiversité et du territoire dans un état en post-conflit : le cas de la Colombie - Luis Fernando Macias Gomez (Études Caribéennes, 2018)
Biodiversity in Colombia has played an important role since the independence until today, in a context of Peace agreements, raising many challenges. Colombia is known as a hyper diverse country. However this wealth has always been apart from the importance that represents. On the one side because of the lack of vision from the government and the conflict that prevented it from being seen with its right dimension.Throughout history the process of occupation of the territory has been complicated and today it is seen with a new intelligibility of the wealth it won’t be. There is an institutional and legal framework since last century that will need to be revised for the new challenges. The future will be complex, but it is hoped to be achieved